A 3D Glacial Isostatic Adjustment model for Northwestern Europe - van Casteren, Rosalie (author) (2019)
The Earth is subjected to 100,000 year cycles of glaciation and deglaciation. The deformations induced by glacial and oceanic loading and the continuous attempt at recovery of the isostatic equilibrium within the solid Earth, are referred to as Glacial Isostatic Adjustment (GIA). This process is ongoing still and yields a large contribution to present day surface deformation and sea level change in formerly glaciated areas. In order to accurately model GIA, the lateral viscosity variations within the interior of the Earth are accounted for (Kaufmann et al., 2000; Steffen et al., 2006; Wu and van der Wal, 2003). Additionally, an increased level of accuracy is obtained by adopting a combination of linear and non-linear viscoelasticity as demonstrated by Barnhoorn et al. (2011); Forno and Gasperini (2007); van der Wal et al. (2013);Wu and Wang (2008). During the Last Glacial Maximum, the British-Irish and Fennoscandian Ice Sheets covered large parts of Northwestern Europe. The interior of the Earth in this area is known to consist of material of very heterogeneous tectonic origin (Artemieva et al., 2006). Additionally, research in this area is promoted by the availability of the independent regional ice model Bradley2018 (Bradley, personal communication), an RSL observation database for the Rhine-Meuse Delta (Hijma and Cohen, 2019), and a collection of GPS derived uplift rates throughout Europe (Teferle, personal communication). At the Astrodynamics and Space Missions research group of Delft University of Technology, a 3D GIA FEM model has been developed to model GIA in Antarctica (Blank et al., 2017). This model follows the work by Wu (2004) and van der Wal et al. (2013), and is complemented with an iterative algorithm to solve the sea level equation in accordance with Kendall et al. (2005). This research aims to provide a single GIA model best suited for the prediction of GIA induced vertical surface deformation in Northwestern Europe, by adapting the existing model. In doing so, a better understanding of the ...